Coexistence of Sjögren syndrome in patients with synovitis, acne, pustulosis, hyperostosis, and osteitis syndrome: A retrospective observational study. Issue 12 (26th March 2021) - Wang, Lun; Yu, Yanying; Zhang, Shuo; Zhang, Wen; Li, Chen
Abstract : Abstract: To identify the prevalence and clinical characteristics of Sjögren syndrome (SS) in a Chinese single-center cohort of synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome. Patients diagnosed with SS were screened out from a cohort of 164 cases of SAHPO syndrome. Information regarding the patients' gender, age at onset, clinical features, laboratory tests, bone scintigraphy, and treatment was reviewed. Five patients were screened out. The prevalence of SS in SAPHO patients was 3.05% The mean onset age of SS was 48.0 ± 12.0 years old and no apparent time order in the occurrence of SAPHO and SS was observed. Compared with the general SAPHO cohort, the 5 SS patients exhibited no significant difference in the SAPHO related clinical features or inflammatory markers, except for a higher prevalence of peripheral joints and bones involvement in bone scintigraphy. Objective evidence of dryness and positive salivary gland biopsy were found in all the patients. However, the positive rates of SSA and SSB antibody were only 20%. Anti-inflammatory treatment for SS was recorded in 3 patients (ESSDAI score: 3 in 2 patients; 12 in 1 patient) with extra-glandular manifestations, severe complications or poor response to the basic treatment. The prevalence of SS is higher in the SAPHO cohort than in the general Chinese population. Objective tests or biopsy might be more indicative than the antibody detection for SS diagnosis. Anti-inflammatory treatment should be prescribed in consideration of both the severity of SS and the demand for disease activity control of SAPHO.